2021
DOI: 10.1007/s11356-021-16429-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industrial effluents on physico-chemical parameters of water and fatty acid profile of fish, Labeo rohita (Hamilton), collected from the Ramsar sites of Punjab, India

Abstract: In this contemporary era, wetlands and the entire aquatic diversity are suffering from major pollution problem. Not only the aggregation of higher population in metropolitan causes the production of plenty of solid, liquid and gaseous wastes, but also the high-technological industries contribute to a mammoth of wastes in the ecosystem. During the process of industrial effluent discharge into the water bodies, the toxic substances available in these wastes can affect the aquatic flora and fauna, resultantly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The burgeoning population of the cities and intensi cation of industries implies that large quantities of solid and/or liquid wastes in the form of either sewage or industrial e uents are released into the water bodies and/or land. The Industrial wastes containing high quantities of dissolved and suspended solids, high Biological Oxygen Demand-(BOD) and Chemical Oxygen Demand-(COD) values, heavy metals, organic and inorganic chemicals, pesticide run-offs, oils and grease harms aquatic life when discharged into the water bodies (Kaur and Brraich 2022). The contaminants gets to accumulate in wetland plants and sediments through such anthropogenic activities, leading to biomagni cation in aquatic organisms, particularly in the tissues of sh.…”
Section: Introductionmentioning
confidence: 99%
“…The burgeoning population of the cities and intensi cation of industries implies that large quantities of solid and/or liquid wastes in the form of either sewage or industrial e uents are released into the water bodies and/or land. The Industrial wastes containing high quantities of dissolved and suspended solids, high Biological Oxygen Demand-(BOD) and Chemical Oxygen Demand-(COD) values, heavy metals, organic and inorganic chemicals, pesticide run-offs, oils and grease harms aquatic life when discharged into the water bodies (Kaur and Brraich 2022). The contaminants gets to accumulate in wetland plants and sediments through such anthropogenic activities, leading to biomagni cation in aquatic organisms, particularly in the tissues of sh.…”
Section: Introductionmentioning
confidence: 99%
“…The studies have also shown that the unsaturated fatty acid content varies significantly depending on the season, which may affect the nutritional properties and storage conditions of fish. In general, a decrease in temperature leads to an increase in the degree of unsaturation [11,12]. In particular, FA composition, degree of unsaturation, and changes in the relative abundance of individual fatty acids have been shown to respond to contamination levels both in experiments and in practise [13,14].…”
Section: Introductionmentioning
confidence: 99%